Efek Potensial Rutin terhadap Kesehatan: Beneficial Health Effects of Routine - Septi Nur Rachmawati; Ruris Haristiani (MPI Press, 2022)
Introduction: Flavonoids are secondary metabolites with flavones core characteristics and C6-C8-C6 carbon branches. Flavonoids have various pharmacological activities, including anticancer, anti-inflammatory, antioxidant, antidiabetic, and antiviral activities through various cell signaling pathways. Rutin is a natural flavonoid derivative that has various health benefits. Many studies have been carried out, both in vitro and in vivo which prove the pharmacological benefits of rutin Objectives: This article aims to describe the pharmacological benefits of rutin. Method: A review of the literature was undertaken using the online databases: BMC, Elsevier, Pubmed, NCBI, Science Direct, and Google scholar. Result: from the literature selected, it was found that rutin has many pharmacological benefits. Conclusion: Beneficial Health Effects of Rutin include antidiabetic, anti-inflammatory, antioxidant, neuroprotective, and Main Protease SARS-CoV-2.